Quel profil du lecteur-apprenant algérien face à un mythe ? - Wassila Soltani (Multilinguales)
By its inscription in an ontological and anthropological dimension, by its ability to lead its reader towards an identification process, the myth is a key to the reading, the comprehension and the interpretation of literary works. Myths are universal vectors of symbolization (fourtanier, 2012 : 23-24). In this sense, what effects could a (re) contextualization of the myth introduce to its reception ? What role can cultural stereotypes play in the reception and interpretation of myths ? Could a character considered immoral, fantastic or absurd, influence us ? Why and how do our attitudes change towards fictional characters ?The reading of myths is a space where all compromises can be articulated. Capital that it is exercised within FFL classes : its support must take into account the dyad (posture of the reader and symbolic-cultural universe of the text).